Bentuk Ketidakadilan Gender dalam Novel Lebih Senyap dari Bisikan Karya Andina Dwifatma: Forms of gender equality in “Lebih Senyap dari Bisikan” novel by Andina Dwifatma - Endriawati, Riskha Anggita; Sulistyorini, Dwi (Himpunan Sarjana Kesusastraan Indonesia (HISKI) Komisariat Kalimantan Timur, 2024)
The basis of this research is to analyze the forms of gender inequality and the main character's efforts to confront these inequalities in the novel Lebih Senyap dari Bisikan. This study employs a qualitative approach by analyzing narrative texts within the story. The data for this research consists of textual excerpts containing instances of gender inequality in the novel Lebih Senyap dari Bisikan. The primary data source is the novel Lebih Senyap dari Bisikan by Andina Dwifatma, which comprised 155 pages and was published by PT Gramedia Pustaka Utama Jakarta in June 2021. The data collection was conducted through library research and note-taking methods. Data analysis procedures for this research involved three phases: data reduction, data presentation, and conclusion. The results of this research indicated various forms of gender inequality in the novel Lebih Senyap dari Bisikan, including (1) marginalization, (2) subordination, (3) stereotypes, (4) violence, and (5) double burden, also the main character's efforts to confront gender inequality are carried-out through seeking power and acquiring strength.